A nitro-capped tetraaniline derivative with AIE features for BSA detection and the selective imaging of Gram-positive bacteria. (8th July 2019) - Liu, Beibei; Wang, Kun; Lu, Hao; Huang, Mingming; Yang, Jiping
Abstract : A nitro-capped tetraaniline derivative (NO2 -B3 -Ani4 -NO2 ) with AIE feature was synthesized and characterized, which presented an ultrasensitive turn-on response towards bovine serum albumin and selective imaging of Gram-positive bacteria based on AIE mechanism. Abstract : A nitro-capped tetraaniline derivative (NO2 -B3 -Ani4 -NO2 ) with aggregation-induced emission (AIE) features was synthesized for the first time, and exhibited red fluorescence in the solid state with a maximum emission wavelength at 640 nm. Moreover, its ultra-sensitive turn-on response towards bovine serum albumin and the selective imaging of Gram-positive bacteria based on an AIE mechanism were investigated, implying its promising application in the biological field.